Developmental Exposure to Environmental Contaminants - Stietz, Kimberly Keil; Baker, Tracie; Plavicki, Jessica (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Development provides an especially sensitive window whereby environmental contaminants can have significant and lasting effects on the morphology and function of many organs and systems. The importance of understanding developmental effects of environmental contaminants extends not only to developmental stages, but also to encompass the hypotheses of the developmental or fetal origins of adult disease. Such effects of environmental contaminants during development extend to health outcomes that can persist in adulthood, first become apparent in adulthood, or manifest in adulthood but only after a second hit/stressor. The diverse nature of possible environmental contaminants, ranging from persistent organic pollutants to emerging contaminants of concern, along with the diverse range of health implications, including autism, diabetes, cancer, infertility, and lower urinary tract function, make understanding developmental effects of environmental contaminants an ever growing and important field of study.This Special Issue aims to explore a variety of topics in line with the aims and scope of Toxics. Specifically, topics related to the developmental effects of environmental contaminants and/or their metabolites on the molecular, cellular, tissue, organ, organ system or organism, including mechanisms of toxicity, metabolism, risk assessment and management, as well as multiple stressor impacts in the context of aging or disease progression following developmental exposures.